Golf-Related Craniofacial Injuries in Adults: A NEISS Database Study. Issue 4 (June 2021) - Brennan, Matthew J.; Fish, Sarah; Cohn, Jason E.; Othman, Sammy; Stucker, Fred J.; Bundrick, Paige
Abstract : Introduction: Despite its popularity, there have been no reports outlining adult craniofacial trauma in the setting of golf injuries. Our main objective was to identify and describe trends in head and neck injuries incurred while participating in golf including injury type, anatomic location, and patient disposition. Methods: A retrospective cohort analysis of the National Electronic Injury Surveillance System (NEISS) was conducted from 2009–2018. Population characteristics of golf-related injuries were recorded, including, age, sex, and race distributions. Distribution of injury anatomic location, injury type, distribution of fracture location, patient disposition was further analyzed. A one way ANOVA was utilized to obtain the mean ages for all injuries and compare them for any statistical difference. To identify statistical significance, a Fisher exact test with a Monte Carlo simulation was performed. Results: A total of 509 golf-related injuries (national estimate 24, 425 cases) were recorded over the study period. Lacerations were the most common injury overall (54.2%), while contusions and abrasions were the next most common injuries (27.3%). The most common fracture subtype observed was midface (40.43%), followed by nasal bone (27.66%), mandible (12.77%), skull (12.77%), and cervical spine (6.38%). The highest proportion of patients admitted for further treatment were individuals >70 years of age. Fractures had the highest rate of admission (29.8%). Conclusions: A better understanding of golf injuries can allow for rapid detection and appropriate treatment when encountered. This knowledge can also help to develop safety precautions by potentially reforming rules and regulations as well as protective equipment. Abstract : Supplemental Digital Content is available in the text